INCREASING OF MOTIVATION TO STUDY FOREIGN LANGUAGES AMONG STUDENTS OF TECHNICAL UNIVERSITIES - Nazarov, Rustam (Журнал иностранных языков и лингвистики, 2023)
The article deals with the problem of motivation in teaching a foreign language to students of technical specialties, which has recently acquired particular relevance due to the increasing role of foreign language communication in the professional activities of modern specialists. The priority of students for external motivation to learn a foreign language is indicated. The requirements of higher education aimed at training competitive specialists who speak foreign languages are taken into account. The ways of increasing students’ interest in studying the subject are considered.